2016
DOI: 10.1073/pnas.1603388113
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide kinetics of DNA excision repair in relation to chromatin state and mutagenesis

Abstract: We recently developed a high-resolution genome-wide assay for mapping DNA excision repair named eXcision Repair-sequencing (XR-seq) and have now used XR-seq to determine which regions of the genome are subject to repair very soon after UV exposure and which regions are repaired later. Over a time course, we measured repair of the UV-induced damage of cyclobutane pyrimidine dimers (CPDs) (at 1, 4, 8, 16, 24, and 48 h) and (6-4)pyrimidinepyrimidone photoproducts [(6-4)PPs] (at 5 and 20 min and 1, 2, and 4 h) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

23
226
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(254 citation statements)
references
References 44 publications
23
226
0
1
Order By: Relevance
“…Thus, by the sheer number of events, a process that itself is hardly mutagenic might become a significant cause for genome alterations. Interestingly, a recent study performed with mammalian cells indicates that, most likely due to delayed damage recognition, NER is slow in heterochromatic regions and leads to the accumulation of a significant number of mutations (35). In this sense, paired SSBs, whether they occur at high frequency in the same strand or at low frequency in opposite strands in close proximity, might be a major threat to genome stability.…”
Section: The Role Of Paired Ssbs On Opposite Strands In the Formation Ofmentioning
confidence: 99%
“…Thus, by the sheer number of events, a process that itself is hardly mutagenic might become a significant cause for genome alterations. Interestingly, a recent study performed with mammalian cells indicates that, most likely due to delayed damage recognition, NER is slow in heterochromatic regions and leads to the accumulation of a significant number of mutations (35). In this sense, paired SSBs, whether they occur at high frequency in the same strand or at low frequency in opposite strands in close proximity, might be a major threat to genome stability.…”
Section: The Role Of Paired Ssbs On Opposite Strands In the Formation Ofmentioning
confidence: 99%
“…In these studies, a high-throughput sequencing method, known as excision repair-sequencing (XR-seq), was used to analyze oligonucleotide fragments excised during NER of CPDs or 6-4PPs. These studies found increased repair activity associated with TC-NER of the TS of actively expressed genes and noncoding transcripts (7,8). There was also more rapid repair in active chromatin domains (i.e., enhancers and promoters) and DNase I hypersensitivity regions, and slower repair associated with repressed and heterochromatin regions (8).…”
mentioning
confidence: 95%
“…These studies found increased repair activity associated with TC-NER of the TS of actively expressed genes and noncoding transcripts (7,8). There was also more rapid repair in active chromatin domains (i.e., enhancers and promoters) and DNase I hypersensitivity regions, and slower repair associated with repressed and heterochromatin regions (8). Reanalysis of these data by other groups indicated that there is decreased repair activity associated with transcription factor binding sites (9) and transcription initiation sites (10), suggesting that NER may be inhibited by the binding of transcription factors and the transcription machinery to DNA.…”
mentioning
confidence: 97%
See 2 more Smart Citations